Bullying intervention through “Writing for Healing” strategy for transformational teachers in Bali - Nia Nafisah; Nita Novianti; Safrina Noorman; Rendila Restu Utami; Bachruddin Musthofa; Ahmad Bukhori Muslim (Universitas Pendidikan Indonesia, 2025)
The rise of student bullying in schools has attracted public attention due to its devastating impact, particularly on victims. Traumatic experiences can be expressed through creative writing to explore emotions and support mental health recovery. In response to the need to raise awareness of the severe impact of trauma on both victims and perpetrators of bullying, the Community Service (PkM) team from the English Language and Literature Study Program at UPI conducted a “Writing for Healing” training for teachers affiliated with the Bali Teacher Movement Center. This activity consisted of five sessions, including material presentations, creative writing practice, and reflections on creative writing experiences to support mental recovery. The training received a positive response from participants, as evidenced by high engagement and the quality of the written products. Several participants also expressed their intention to publish their work. Thus, this training has created a pathway to address bullying and can be used by teachers in schools. It is hoped that this activity will help teachers address bullying cases while also raising awareness of its impacts and alternative solutions. Abstrak Maraknya perundungan murid di sekolah menjadi perhatian masyarakat karena berdampak buruk, khususnya bagi korban perundungan. Pengalaman traumatis dapat dicurahkan dalam tulisan kreatif sebagai sarana mengeksplorasi perasaan dan menjadi alat pemulihan kesehatan mental. Berkaitan dengan perlunya kesadaran akan dampak buruk trauma yang dialami korban dan pelaku remaja yang terlibat perundungan, tim Pengabdian kepada Masyarakat (PkM) Prodi Bahasa dan Sastra Inggris UPI menyelenggarakan pelatihan “Writing for Healing” untuk para guru yang bergabung dengan Balai Guru Penggerak Bali. Kegiatan ini dilakukan sebanyak lima kali pertemuan yang terdiri dari pemaparan materi, praktik menulis kreatif, dan refleksi pengalaman menulis kreatif untuk pemulihan mental. Hasil pelatihan menunjukkan adanya respons positif dari peserta dalam bentuk tingkat partisipasi yang baik dan kualitas produk tulisan yang dibuat. Beberapa peserta juga berniat untuk mempublikasikan karya tulis mereka. Dengan demikian, pelatihan ini telah membuka salah satu jalan dalam upaya penanganan perundungan dan dapat dimanfaatkan oleh para guru di sekolah. Melalui kegiatan ini diharapkan dapat membantu para guru untuk dapat memberikan penanganan terhadap kasus perundungan, sekaligus meningkatkan kesadaran akan dampak perundungan dan alternatif penyelesaiannya. Kata Kunci: menulis kreatif; pemulihan kesehatan mental; perundungan; sekolah